The Effect of Digital Learning Innovation on Enhancing Deep Learning and Student Engagement in Secondary Schools - Erlina Cahyana (Proceeding of the International Conference on Global Education and Learning, 2025)
The rapid advancement of digital technology has transformed the landscape of education, particularly in secondary schools. This study investigates the influence of digital learning innovation on enhancing deep learning and student engagement. Using a quantitative survey method, data were collected from 150 secondary school students in Indonesia who actively use digital learning platforms such as Learning Management Systems (LMS), mobile learning applications, and hybrid learning models. The research instrument consisted of a closed-ended questionnaire using a five-point Likert scale, which measured students’ perceptions of digital learning innovation, their engagement levels, and indicators of deep learning. Data were analyzed through simple linear regression using SPSS version 25. The results indicate a strong and significant positive relationship between digital learning innovation and both deep learning and student engagement, with a correlation coefficient (R) of 0.732 and an R² value of 0.536. This finding suggests that digital learning innovation explains 53.6% of the variation in students’ deep learning and engagement levels. Students who frequently use digital learning technologies tend to show higher motivation, independence, critical thinking, and reflective learning behavior. The study concludes that digital learning innovation plays a crucial role in supporting meaningful learning and active participation. It highlights the importance of integrating technology strategically into school-based learning to foster adaptive, collaborative, and lifelong learners in the digital era.